Mobile-banking’s User Readiness To Reuse Self Service Technology - Eni Munarsih (EBBANK, 2014)
This research aims to test m-banking user readiness to utilize m-banking services and to test the effects of perceived service quality variable and satisfaction with m-banking services as the variable mediating relationship between the of m-banking user readiness and the sustainable intention to reuse m-banking services. Variables being controlled in this research were gender and education level. Data were collected by distributing questionnaires to respondents determined by means of a purposive sampling technique, namely customers that have frequently used m-banking services. Meanwhile, the data were drawn by means of a convenience method. There were 110 exemplars of questionnaire distributed to the respondents but only 92 exemplars were used for analysis.            A Structural Equation Model was used to analyze the data by means of a PLS alternative method aided by an application program of SmartPLS. The M-banking user readiness and perceived service quality variables were tested using a second order factor approach, meanwhile the other variable, namely satisfaction with m-banking services and sustainable intention to reuse m-banking services were tested using a first order factor approach.            Results of the analysis showed that the m-banking user readiness had a positive and significant relation to the sustainable intention to reuse m-banking services. The relation would be more robust when it was mediated by the perceived service quality. The use of a control variable over the m-banking user readiness did not exert a significant effect on the readiness of users and did not change the relation between the variables.